Level of Satisfaction Among Patients Using Insulin Administered by Pen vs Vial/Syringe. An Observational Prospective Study - Valladales-Restrepo LF; Delgado-Araujo AC; Oyuela-Gutiérrez MC; Ospina-Arzuaga HD; Machado-Alba JE (Patient Preference and Adherence)
Luis Fernando Valladales-Restrepo,1– 3 Ana Camila Delgado-Araujo,1 María Camila Oyuela-Gutiérrez,3 Harrison David Ospina-Arzuaga,1 Jorge Enrique Machado-Alba1 1Grupo de Investigación en Farmacoepidemiología y Farmacovigilancia, Universidad Tecnológica de Pereira-Audifarma S.A, Pereira, Risaralda, Colombia; 2Grupo de Investigación Biomedicina, Facultad de Medicina, Fundación Universitaria Autónoma de las Américas, Pereira, Colombia; 3Semillero de Investigación en Farmacología Geriátrica, Facultad de Medicina, Fundación Universitaria Autónoma de las Américas, Pereira, Risaralda, ColombiaCorrespondence: Jorge Enrique Machado-Alba, Grupo de Investigación en Farmacoepidemiologia y Farmacovigilancia. Universidad Tecnologica de Pereira-Audifarma SA., Calle 105 No. 14-140, Pereira, Risaralda, 660003, Colombia, Email machado@utp.edu.coPurpose: To determine the satisfaction of patients with diabetes mellitus who used subcutaneous insulin application devices in Colombia.Patients and Methods: An observational prospective study of patients with diabetes mellitus receiving insulin treatment in Colombia. Sociodemographic, comorbidity and pharmacological data were taken from a drug dispensing database. Through telephone calls, satisfaction with application devices was evaluated with Diabetes Treatment Satisfaction Questionnaire status version (DTSQ-s). Satisfaction was considered high at a score ≥ 30 points. The change in the type of insulin delivery device (ie, from pen to vial/syringe, and from vial/syringe to pen) was evaluated during a 1-year follow-up.Results: A total of 382 patients from 75 cities were selected, with a median age of 66.0 years, and 56.3% were women, and 65.2% were treated with long-acting insulins. The mean DTSQ-s score was 26.6± 5.3 points, and 38.7% presented high satisfaction, without statistically significant differences between pen and vial/syringe. A total of 18.8% changed the administration device, mainly those that came from Bogotá-Cundinamarca (OR:2.19; 95% CI:1.01– 4.75), in concomitant treatment with other antidiabetic drugs (OR:2.28; 95% CI:1.00– 5.22) and those who previously used insulin in vial/syringe (OR:33.90; 95% CI:11.88– 96.74).Conclusion: The participants had low satisfaction with the insulin delivery device. No statistically significant differences were found in satisfaction between those who received pen vs vial/syringe insulin, and patients using the latter had a high probability of switching to insulin pen.Keywords: (MeSH): diabetes mellitus, patient satisfaction, insulin, long-acting, insulin, short-acting, pharmacoepidemiology